PERTIMBANGAN HAKIM DALAM PENETAPAN DISPENSASI NIKAH DIMASA PANDEMI COVID-19 - Gabriel Sheva Rahardjo (2022)
This thesis aims to explain the considerations of the Council of Judges of the Religious Courts During the Covid 19 Pandemic, in determining marriage dispensation cases that have not yet entered the age of marriage, and after the amendment of the Marriage Law No. 1 of 1974 to Law No. 16 of 2019, changes occurred in the number The age of marriage for women who are equal to men is 19 years, and this regulation is implemented to overcome the emergency conditions of child marriage that occur in Indonesia. However, the increase in the number of cases applying for a marriage dispensation was not accompanied by strict rules, so that the majority of those who submitted the application were granted by the judge, the existing regulations, both Law no. 16 of 2019 and PERMA No. 5 of 2019 has a legal loophole that makes marriage dispensation permits still wide open for any reason The research method in this research is normative juridical research, so the data collection method used is through library research. In addition, as a source of research data, the authors also use the results of interviews as additional data to deepen the research results. Data collection through the interview mechanism was carried out directly (Library Research) by involving the judges of the Tigaraksa Religious Court with a time and place located at the Tigaraksa Religious Court in terms of marriage dispensation and regulation Mahkamah Konstitusi No.5 Tahun 2019.